Maximizing Productivity: HR Competence, EI, Work Ethic, and Motivation: Mengoptimalkan Produktivitas: Kompetensi HR, Kecerdasan Emosional, Etika Kerja, dan Motivasi - Sigit Dwi Subandi; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2022)
This quantitative study investigated the impact of HR competence, emotional intelligence, and work ethic on work productivity, with motivation serving as an intervening variable. The research was conducted among employees of a production division in a manufacturing company. Data from a sample of 60 employees were collected through interviews and questionnaires and analyzed using Structural Equation Modeling (SEM) PLS. The findings revealed that HR competence, emotional intelligence, and work ethic significantly and positively influenced both productivity and motivation. Furthermore, motivation had a significant positive effect on productivity. Notably, emotional intelligence exhibited a significant positive effect on productivity when mediated by motivation. However, the study found no significant influence of competence and work ethic on productivity when motivation acted as an intervening variable. These results highlight the importance of fostering emotional intelligence and motivation to enhance employee productivity in the workplace, suggesting potential implications for organizational practices and management strategies. Highlights: The study examines the impact of HR competence, emotional intelligence, and work ethic on work productivity. Motivation is explored as a catalyst in enhancing productivity among employees. The findings highlight the significance of emotional intelligence and motivation in improving workplace productivity. Keywords: Workforce Potential, HR Competence, Emotional Intelligence, Work Ethic, Motivation